Long-Term PDE-5A Inhibition Improves Myofilament Function in Left and Right Ventricular Cardiomyocytes through Partially Different Mechanisms in Diabetic Rat Hearts - Beáta Bódi; Árpád Kovács; Hajnalka Gulyás; Lilla Mártha; Attila Tóth; Csaba Mátyás; Bálint András Barta; Attila Oláh; Béla Merkely; Tamás Radovits; Zoltán Papp (MDPI AG, 2021)
Heart failure with preserved ejection fraction (HFpEF) and right ventricular (RV) dysfunction are frequent complications of diabetic cardiomyopathy. Here we aimed to characterize RV and left ventricular (LV) remodeling and its prevention by vardenafil (a long-acting phosphodiesterase-5A (PDE-5A) inhibitor) administration in a diabetic HFpEF model. Zucker Diabetic Fatty (ZDF) and control, ZDF Lean (Lean) male rats received 10 mg/kg vardenafil (ZDF + Vard; Lean + Vard) per os, on a daily basis for a period of 25 weeks. In vitro force measurements, biochemical and histochemical assays were employed to assess cardiomyocyte function and signaling. Vardenafil treatment increased cyclic guanosine monophosphate (cGMP) levels and decreased 3-nitrotyrosine (3-NT) levels in the left and right ventricles of ZDF animals, but not in Lean animals. Cardiomyocyte passive tension (Fpassive) was higher in LV and RV cardiomyocytes of ZDF rats than in those receiving preventive vardenafil treatment. Levels of overall titin phosphorylation did not differ in the four experimental groups. Maximal Ca2+-activated force (Fmax) of LV and RV cardiomyocytes were preserved in ZDF animals. Ca2+-sensitivity of isometric force production (pCa50) was significantly higher in LV (but not in RV) cardiomyocytes of ZDF rats than in their counterparts in the Lean or Lean + Vard groups. In accordance, the phosphorylation levels of cardiac troponin I (cTnI) and myosin binding protein-C (cMyBP-C) were lower in LV (but not in RV) cardiomyocytes of ZDF animals than in their counterparts of the Lean or Lean + Vard groups. Vardenafil treatment normalized pCa50 values in LV cardiomyocytes, and it decreased pCa50 below control levels in RV cardiomyocytes in the ZDF + Vard group. Our data illustrate partially overlapping myofilament protein alterations for LV and RV cardiomyocytes in diabetic rat hearts upon long-term PDE-5A inhibition. While uniform patterns in cGMP, 3-NT and Fpassive levels predict identical effects of vardenafil therapy for the diastolic function in both ventricles, the uneven cTnI, cMyBP-C phosphorylation levels and pCa50 values implicate different responses for the systolic function.